The North Pole aftermath : speech of Hon. S. D. Fess, of Ohio, in the House of Representatives, Congress of the United States, Thursday, March 4, 1915. - Fess, Simeon D. (Simeon Davidson), 1861-1936. ([Washington : U. S. Govt. Print. Off., 1915)
Mode of access: Internet.